An Analytical Investigation to Select a Suitable Site for Reservoir to Meet the Challenges of Water Scarcity in Rural Areas of Tripura - Bhowmik, Saumyadeep; Shukla, Bishnu Kant; Kumar, Murari (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963383);" role="presentation">The provision of safe drinking water supply and sanitation facilities is a basic ne<span dir="ltr" style="left: calc(var(–scale-factor)*409.63px); top: calc(var(–scale-factor)*302.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976212);" role="presentation">cessity of life and a crucial <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977534);" role="presentation">input in achieving the goal of health for all. <span dir="ltr" style="left: calc(var(–scale-factor)*257.81px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955346);" role="presentation">Tripura is rich in natural resources but <span dir="ltr" style="left: calc(var(–scale-factor)*421.03px); top: calc(var(–scale-factor)*315.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960877);" role="presentation">due to lack of storage of <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915526);" role="presentation">runoff and also due to the increasing level of urbanization, <span dir="ltr" style="left: calc(var(–scale-factor)*308.33px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90807);" role="presentation">the retention <span dir="ltr" style="left: calc(var(–scale-factor)*361.15px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889971);" role="presentation">capacity of the watersheds in these a<span dir="ltr" style="left: calc(var(–scale-factor)*507.22px); top: calc(var(–scale-factor)*329.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.830514);" role="presentation">reas <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922732);" role="presentation">is <span dir="ltr" style="left: calc(var(–scale-factor)*82.22px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955233);" role="presentation">receding day by day. As the pattern of climate is also changing<span dir="ltr" style="left: calc(var(–scale-factor)*345.79px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949256);" role="presentation">, a <span dir="ltr" style="left: calc(var(–scale-factor)*359.95px); top: calc(var(–scale-factor)*342.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944289);" role="presentation">drought like situation seems to be most <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898205);" role="presentation">probable in such areas. In this regard, <span dir="ltr" style="left: calc(var(–scale-factor)*225.17px); top: calc(var(–scale-factor)*355.61px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938764);" role="presentation">the technological advancements of Artificial Neural Network (ANN) were <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915986);" role="presentation">implemented to achieve selecte<span dir="ltr" style="left: calc(var(–scale-factor)*199.97px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954298);" role="presentation">d objectives of reservoir site identification. <span dir="ltr" style="left: calc(var(–scale-factor)*379.63px); top: calc(var(–scale-factor)*368.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946433);" role="presentation">This study is focused to store rural <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*382.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920657);" role="presentation">water in a reservoir like structure at a suitable site to facilitate supply to rural and urban area during dry season. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945528);" role="presentation">The rank of each parameter <span dir="ltr" style="left: calc(var(–scale-factor)*192.65px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875648);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*212.33px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961339);" role="presentation">also obtained using fu<span dir="ltr" style="left: calc(var(–scale-factor)*305.21px); top: calc(var(–scale-factor)*395.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979799);" role="presentation">zzy logic decision making and Analytical Hierarchy <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*408.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920245);" role="presentation">Process. Using these weights reservoir site Identification was developed by AHP and Fuzzy logic and predicted <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*421.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00053);" role="presentation">for Gomati River. <span dir="ltr" style="left: calc(var(–scale-factor)*151.34px); top: calc(var(–scale-factor)*421.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976904);" role="presentation">At the end, a reservoir was designed at the suitable location having pre defi<span dir="ltr" style="left: calc(var(–scale-factor)*475.78px); top: calc(var(–scale-factor)*421.75px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902116);" role="presentation">ned storage <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*434.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904551);" role="presentation">capacity to cater the needs of the local population